Relação K:Ca:Mg na solução nutritiva para a produção de minitomate cultivado em substrato - Abrahão, Camila [UNESP]; Villas Bôas, Roberto Lyra [UNESP]; Bull, Leonardo Theodoro [UNESP] (My University, 2014)
The study was conducted to evaluate six K:Ca:Mg ratios for production of two cultivars of mini tomato grown in substrate, in a greenhouse, during two growing seasons. The experimental design was randomized blocks with four replications and twelve treatments using both cultivars of mini tomato (Sweet Million and Sweet Grape) and six K:Ca:Mg ratios (4:3:1, 6:3:1, 6:4.5:1, 2.7:3:1, 2.7:2:1, 4:2:1) in nutrient solutions. In both experiments, nutrient solutions with the highest concentrations of Mg, (75 mg L-1) and the lowest concentrations of Ca, (150 mg L-1) led to the highest concentrations of those nutrients in plant dry matter. The Sweet Million cultivar had higher yield (1.69 kg plant-1 and 1.52 kg plant-1), number of fruits per plant (227 and 236), and water use efficiency (29.1 kg m-3 and 25.3 kg m-3). However, the Sweet Grape cultivar had fruits of higher mean weight (9.0 g and 8.8 g) and macronutrient content in the leaves. In both crop cycles, the different K:Ca:Mg ratios affected only the macronutrient contents of the mini tomato plants grown in substrate, with no effect on yield and water use efficiency. The first crop cycle showed the highest N, K, Ca and S content.
K:Ca:Mg ratio in nutrient solution for production of mini tomato grown in substrate
Keywords: Coconut fiber; Fertigation; Greenhouse; Plant nutrition; Solanum lycopersicum